Strategic networks and alliances among tourism MSMEs: the case of Dubai’s “Wander With” - Badran, Badran; Badran, Nada B (Piccola Impresa / Small Business, 2019)
Abstract The aim of this study is to discuss the role of networks and strategic alliances in the life of small enterprises working in tourism. This is done by presenting a case study that discusses the experience of Wander With, a micro SME that operates in Dubai’s young, multinational tourism market. It investigates the criteria for an MSME to select partners and alliances, the challenges and risks an MSME faces while dealing with networks and alliances, the benefits an MSME obtains from networks and alliances, the extent to which the Dubai tourism market is connected with the global market, and the tools an MSME uses to become known and generate business globally. Among the general findings of this study is that the main impetus for MSMEs to develop strategic alliances with other organizations is to marshal resources and leverage mutual support. Cooperation among various MSMEs increases their innovation and profitability. Moreover, networking among diverse partners is essential to supply integrated tourist products and provide optimum services to tourists. Finally, Dubai MSMEs have a low scalability potential due to prevalence of high overhead structures, coupled with high existing capacity utilization levels. This case study fills a gap in the research about MSMEs in tourism in the Arab Gulf region, specifically about the role networks and alliances play in their business model